The favourite [videorecording (DVD)] - Colman, Olivia; Stone, Emma, 1988-; Weisz, Rachel, 1970- (20th Century Fox Home Entertainment, 2019)
Early eighteenth-century England is at war with the French. A frail Queen Anne occupies the throne, and her friend Lady Sarah tends to her ill health. When a new servant Abigail arrives, Sarah takes her under her wing, and Abigail sees a chance at a return to her aristocratic roots. As the politics of war become time-consuming for Sarah, Abigail steps in to fill in as the Queen's companion. Their growing friendship gives her a chance to fulfill her ambitions, and no one will stand in her way.